2020
DOI: 10.1101/2020.03.23.002899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mass spectrometric characterisation of the circulating peptidome following oral glucose ingestion in control and gastrectomised patients

Abstract: Meal ingestion triggers secretion of a variety of gut and endocrine peptides, several of which are routinely measured in research studies by commercial immunoassays. We developed an LC-MS/MS based assay for parallel monitoring of multiple peptides in small volumes of human plasma, providing the benefit of analysing exact peptide sequences rather than immuno-reactivity, and potential advantages of cost and sample volumes for measuring multiple peptide hormones. The method involves acetonitrile precipitation of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…At these heightened concentrations, untargeted approaches can detect and quantify them to compare plasma levels during an oral glucose tolerance test. 126…”
Section: Diabetes and Gut Hormonesmentioning
confidence: 99%
“…At these heightened concentrations, untargeted approaches can detect and quantify them to compare plasma levels during an oral glucose tolerance test. 126…”
Section: Diabetes and Gut Hormonesmentioning
confidence: 99%
“…A study of healthy volunteers found that consumption of a meal with a high glycemic index was associated with a blunted release of motilin compared to a meal with a low glycemic index [124]. Similarly, the consumption of glucose in diabetic patients undergoing a glucose tolerance test resulted in a significant decrease in plasma motilin [125]. In contrast, the administration of prebiotics resulted in increases in motilin levels in an animal model of constipation [126].…”
Section: Conceptual Analysis Of the Links Between Motilin And Depressionmentioning
confidence: 99%
“…As this bioanalytical technique is readily multiplexable, it was simultaneously developed for the comeasurement of insulin, C-peptide, GIP (1-42) and GIP . Bioactive GIP(1-42) only circulates for a short time before inactivation by dipeptidyl peptidase IV to produce inactive GIP (3-42) (19); the use of targeted LC-MS/MS provides the opportunity to quantify both GIP isoforms simultaneously due to their difference in molecular weight, as described in previous LC-MS/ MS protocols (20)(21)(22). Immunoassay analysis was additionally performed for active ghrelin and total GIP, to correlate ghrelin and motilin profiles, and compare the different methods for GIP detection.…”
Section: Introductionmentioning
confidence: 99%